2020
DOI: 10.1002/alz.12035
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic assessment of suvorexant in patients with probable Alzheimer's disease dementia and insomnia: a randomized trial

Abstract: Introduction We evaluated the clinical profile of the orexin receptor antagonist suvorexant for treating insomnia in patients with mild‐to‐moderate probable Alzheimer's disease (AD) dementia. Methods Randomized, double‐blind, 4‐week trial of suvorexant 10 mg (could be increased to 20 mg based on clinical response) or placebo in patients who met clinical diagnostic criteria for both probable AD dementia and insomnia. Sleep was assessed by overnight polysomnography in a sleep laboratory. The primary endpoint was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 45 publications
1
71
1
1
Order By: Relevance
“…A particular target for DO-RAs use are patients with Alzheimer's dementia, and other types of dementia. Double blind studies of use of suvorexant in patients with this disorder showed improved sleep and side effects that were comparable to those seen in general population who use this medication [24] . DORAs could be further useful in treating accompanying symptoms, such as delirium and circadian rhythm disruptions.…”
supporting
confidence: 56%
“…A particular target for DO-RAs use are patients with Alzheimer's dementia, and other types of dementia. Double blind studies of use of suvorexant in patients with this disorder showed improved sleep and side effects that were comparable to those seen in general population who use this medication [24] . DORAs could be further useful in treating accompanying symptoms, such as delirium and circadian rhythm disruptions.…”
supporting
confidence: 56%
“…Encouragingly, studies involving older healthy participants have not demonstrated significantly different efficacy or safety outcomes [145,150], and the sole trial in a neurodegenerative cohort that has been published to date has suggested strikingly similar outcomes to those in healthy cohorts. In this randomized controlled trial undertaken in patients with insomnia and mild-moderate Alzheimer's [151], orexin antagonism was superior to placebo with respect to improvements in total sleep time (73 min vs 45 min) and wake time after sleep onset (− 45 min vs -29 min), with no major effect on sleep architecture. Moreover, limited cognitive assessment through the Mini Mental State Examination and Symbol Digit Task did not suggest deleterious cognitive outcomes, somnolence was not prominent or severe, and while there were more falls in the treatment group (2.1% vs 0%), these were not judged to be drug related.…”
Section: Orexin Antagonistsmentioning
confidence: 93%
“…Based on this evidence, DORAs have been hypothesized as a possible treatment for either sleep impairment or neurodegenerative processes in AD patients. The first polysomnographic assessment of suvorexant in AD patients co-affected by insomnia documented the efficacy of this drug with a noted increase of total sleep time and sleep efficiency (Herring et al, 2020). This result was expected as the association between sleep impairment and CSF OX levels had been previously documented in AD patients .…”
Section: Human Studiesmentioning
confidence: 72%